A case–control study regarding relative factors for behavioural and psychological symptoms of dementia at a Canadian regional long‐term extended care facility: a preliminary report. Issue 1 (8th January 2014) - Sawa, Minoru; Chan, Peter; Donnelly, Martha; McKenna, Mario; Osaki, Yoneatsu; Kishimoto, Takuji; Ganesan, Soma
Abstract Background Behavioural and psychological symptoms of dementia (BPSD) are prevalent and have an impact on the care of persons with dementia. Previous studies regarding predisposing factors have included pharmacotherapy, but other factors may not have been sufficiently studied. We hypothesized that psychotropic medications, past history, comorbid psychiatric disorders and other factors may be relevant factors related to BPSD. Methods Data were collected from patients' medical charts at an extended care facility over a 2‐year period from 1 May 2008 to 30 April 2010. Information obtained included the presence of BPSD, gender, age, marital status, past history, comorbid psychiatric disorder and medication use. Patients were divided into two groups: a group with BPSD (n = 29) and a group without BPSD (n = 10). A binomial logistic regression analysis was performed for the above factors. Results Comorbid major depression was linked to BPSD (odds ratio = 12.57, 95% confidence interval: 1.31–120.74) as well as to the use of antidepressants (odds ratio = 6.49, 95% confidence interval: 1.02–41.25). There was a trend towards statistical significance in the relationship between greater use of antidepressants for the patients with comorbid major depression and the presence of BPSD. Past history of depression (Fisher's exact test; P = 0.03) and cerebral vascular accident (degrees of freedom = 1, χ2 = 4.44, P = 0.04) were linked to the presence of BPSD and comorbid major depression. Conclusion Accurate evaluation and treatment of comorbid major depression may affect BPSD. In order to reduce the burden of BPSD on patients and caregivers, there should be a careful and thoughtful diagnosis of comorbid major depression in patients with dementia.